Effectiveness of amine fluoride mouthwash in preventing white spot lesions during fixed orthodontic therapy - A randomized control trial - K R Ravi Kiran; Sharanya Sabrish; Silju Mathew; Prashantha G Shivamurthy; Roshan Sagarkar (Wolters Kluwer Medknow Publications, 2023)
Background and Aim: One of the main reasons that patients seek orthodontic treatment is aesthetics. Unfortunately, treatment with fixed orthodontic appliances can at times increase the chances of developing white spot lesions on the surfaces of teeth, thus creating a new aesthetic issue for the patient. The prevalence of white spot lesions (WSL) reported after treatment varies from 2% to 97%, and these lesions can occur despite increased attention to hygiene. Hence the aim of this study was to assess the effect of Amine fluoride mouthwash in preventing white spot lesions during fixed orthodontic therapy. Materials and Methods: Study participants were randomly divided into two groups (Group A - experimental 25 patients and Group B - control 25 patients). The pre-intervention and post-intervention intra-oral digital photographs were analysed by using ImageJ software to assess the percentage of the facial surface affected on the teeth (10 maxillary teeth), which had white spot lesions. Results: The mean value of WSLs showed significant difference between the experimental and control groups. Mean values of WSL in the experimental group decreased from 2 to 1.54 with a mean difference of 0.46 after 6 months of follow-up which indicated that amine fluoride mouthwash was effective in preventing WSLs during fixed orthodontic treatment. Conclusion: WSLs scores were significantly reduced in patients who received the mouthwash when compared to patients who followed standard oral hygiene regimen with fluoridated toothpaste only. In clinical practice, amine fluoride mouthwash is an effective method for the prevention of WSLs during fixed orthodontic treatment.